HOMESTAY INNOVATION CAPABILITY IN A PROPERTY BUSINESS PERSPECTIVE - Priyatiningsih, Katharina (International Journal of Sustainable Competitiveness on Tourism, 2022)
The rapid development of entrepreneurship-based tourism has encouraged households in tourist areas to try to take advantage of opportunities to do business through residential property to become homestays. Homestays are offered for tourists who want to spend the night naturally, enjoy daily life with the local culture of the destination visited with all the facilities which of course can meet the needs of traveling. Residential home owners try to become property entrepreneurs by understanding the management of the property business through innovation capabilities that transform residential homes into homestays. The needs of tourists in choosing homestay accommodation are different from hotels or villas or bungalows, preferring to enjoy a homely atmosphere by getting memories and local experiences in tourist destination areas. Residential homeowners will seek information regarding home repairs and the physical availability of residential homes, arrange schedules, and need to study property management in collaboration with residential developers. So this study aims to determine the innovation ability of homestay property developers who are considered influential in increasing business through the dimensions of technology development, operational capabilities, managerial routines and property transactions. This descriptive research with quantitative and qualitative approaches uses triangulation data collection techniques and is statistically analyzed using Partial Least Square. It is important for homestay business owners to find building developers who can repair or rearrange buildings who have the ability to innovate in the property business. The results of measurements from residential home owners and property developers in tourist destinations show that the dimensions of strong property innovation capabilities are innovation capabilities in management and routine operations, while the dimensions of innovation capabilities that still have weaknesses are innovation capabilities in technology development and transactions. Keywords: Innovation capability; homestays ; Property Business.